Analisis Kinerja Karyawan Dalam Meningkatkan Kepuasan Pelanggan Terhadap Usaha Yolla Laundry - Ratu Dara Saphira; Rahmat Hafiz Audia; Rindu Anggelina Wiljon; Roby Mardiansyah Putra; Vivi Nila Sari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstrak. In this modern era, women have the same opportunities as men to have a career outside the home. This causes the housework to no longer be handled entirely by the mother. One of the modern lifestyles of city residents is washing clothes in special places or known as laundries. In big cities especially, laundry outlets continue to grow. Kilo laundry is also the right choice for those who want to open this type of business with not too much capital. With the capital of a washing machine and adequate business space, and supported by a strategic location, it can create prospects. The laundry business opportunity is a business opportunity that quite a lot of people are currently developing. Laundry is a form of service for those who always want life to be easier. Locations that business owners can use as a place to manage their landry business are areas where clean water is difficult. Areas where clean water is difficult are in dire need of laundry businesses, especially for immigrants who feel uncomfortable with the water conditions. Tourism areas are also special areas that are quite effective for managing a laundry business. In tourist areas, people usually set laundry rates at quite expensive prices. The opportunity for a managed laundry business will be able to grow rapidly if it is able to maximize service to customers, both in terms of quality of laundry results, timeliness and friendliness of the waiters. If the business owner is able, it would be better to offer and provide excellent service in the form of picking up and delivering laundry products to affordable customer addresses. To develop laundry business opportunities, business owners can also collaborate with parties such as hotels, this will be more effective carried out in tourism areas.